Association Between Blood Lead Level With High Blood Pressure in US (NHANES 1999–2018) - Huang, Ziyao (Frontiers in Public Health, 2022)
Background Lead is a toxic metal for human health, but the effect on blood pressure (BP) is still controversial. The object of this study was to demonstrate the association between blood lead levels with BP and hypertension (HTN). Methods We used the database from the National Health and Nutrition Examination Survey (NHANES, 1999–2018) to perform a cross-sectional study. We performed multivariate regressions to examine the association between blood lead level with HTN and BP, and then a subgroup analysis was performed. Results A total of 32,289 participants were included in this study, but no significant difference was found between blood lead levels and HTN. However, the association between blood lead levels with systolic and diastolic pressure became positive. In the subgroup analysis stratified by race, the association between non-Hispanic white and black people still existed. Conclusion The association between blood lead levels with HTN was not significant, but it was positively associated with BP. Besides, the association between non-Hispanic white and black people was also significant.